Designing the Montessori Coaching Tool Elementary Rubric for Early-Career Professional Development - Murray, Angela; Daoust, Carolyn; Mallett, Jan (Journal of Montessori Research, 2021)
Becoming a competent Montessori Elementary guide is a complex process, so we are developing the Montessori Coaching Tool Elementary (MCT-EL) rubric to describe teaching-practice expectations for self-reflection and formative feedback during the critical early period in a teacher’s development. The purpose of this article is to share results from a small-scale, online survey collecting both qualitative and quantitative feedback on the rubric from experienced Montessori Elementary teacher educators. The rubric’s content was based on Maria Montessori’s writings and welldocumented Montessori practices, which we translated to specific teacher behaviors and developmental progressions. We wanted to gauge the MCT-EL rubric’s usefulness and appropriateness from the perspective of experts who have significant depth of experience mentoring new teachers. The rubric was not developed to be used for performance evaluation, promotion, or retention but rather for early-career Montessori teachers’ self-reflection. It provides a framework for coaching conversations between the early-career Montessori teacher and a Montessori mentor. Results from the study identified overall support for use of the MCT-EL rubric with developing teachers, along with specific recommendations for revisions, additions, and deletions. Using a thorough review of the data, we developed a refined MCT-EL rubric, which is provided in Appendix B and is available for use by interested practitioners in the field.